Selective visual attention computatuonal models and applications - Zhang, Liming (John Wiley, 2013)
Visual attention is a relatively new area of study combining a number of disciplines: artificial neural networks, artificial intelligence, vision science and psychology. The aim is to build computational models similar to human vision in order to solve tough problems for many potential applications. This book provides an up-to-date and highly applied introduction to this topic, aiding researchers in creating powerful computer vision systems and practicing engineers looking for techniques involving the application of image coding, video processing, machine vision and brain-like robots.